Emergence of Rechargeable Aqueous Manganese Batteries - Xu, Zikang; Long, Lifen; Yang, Ying; Cao, Zeyu; Ren, Hang; Wei, Zhixuan; Shen, Laifa; Jiang, Heng; Shao, Huaiyu; Dong, Shengyang (Nano-Micro Letters, 2026)
Manganese exhibits remarkable chemical versatility, arising from its multiple valence states and diverse coordination environments. This unique redox flexibility underpins a rich spectrum of electrochemical processes, making manganese-based compounds central to the development of advanced energy storage systems. However, it also gives rise to intrinsic instability, involving disproportionation reactions, dissolution of Mn species, and irreversible structural evolution. An in-depth understanding of these coupled chemical–structural dynamics is essential to unlocking the full potential not only of Mn-based electrodes but, more importantly, of aqueous Mn-ion batteries (AMIBs). In this review, we critically summarize the recent progress of AMIBs, with an emphasis on the development and engineering strategies of electrodes and electrolytes. Finally, we propose future perspectives for constructing robust, energetic, and sustainable AMIBs. Highlights: 1 A systematic elucidation of the fundamental electrochemical principles governing aqueous manganese batteries, focusing on the reaction mechanisms of key redox couples (e.g., Mn/Mn2+/Mn3+/MnO2), carrier characteristics (such as ionic radius and solvation effects), and their underlying impact on battery performance. 2 A comprehensive and focused overview of recent advances in electrodes and electrolytes, including key modification strategies—pre-intercalation, coating, and interface regulation on electrode materials and optimizing electrolyte components (e.g., pH, additives) to suppress side reactions and widen the electrochemical window. 3 A systematic analysis of the core challenges hindering the practical application, such as irreversible deposition/dissolution and electrode structural degradation. The future research directions were proposed, including electrode/electrolyte optimization strategies, characterization methods, and AI-assisted approaches, etc.